1993
DOI: 10.1016/0550-3213(93)90166-m
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally-invariant k⊥-clustering algorithms for hadron-hadron collisions

Abstract: We propose a version of the QCD-motivated`k ? ' jet-clustering algorithm for hadron-hadron collisions which i s i n v ariant under boosts along the beam directions. This leads to improved factorization properties and closer correspondence to experimental practice at hadron colliders. We examine alternative denitions of the resolution variables and cluster recombination scheme, and show that the algorithm can be implemented eciently on a computer to provide a full clustering history of each e v ent. Using simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
1,176
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,227 publications
(1,184 citation statements)
references
References 38 publications
(45 reference statements)
4
1,176
0
4
Order By: Relevance
“…These studies demonstrated that the k T cluster algorithm [21] in the longitudinally invariant inclusive mode [22] is at present the method to reconstruct jets in ep collisions for which the smallest uncertainties are achieved. Previous analyses were done with jet radius R = 1, where R is the maximum distance in the pseudorapidity (η)-azimuth (φ) plane for particle recombination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated that the k T cluster algorithm [21] in the longitudinally invariant inclusive mode [22] is at present the method to reconstruct jets in ep collisions for which the smallest uncertainties are achieved. Previous analyses were done with jet radius R = 1, where R is the maximum distance in the pseudorapidity (η)-azimuth (φ) plane for particle recombination.…”
Section: Introductionmentioning
confidence: 99%
“…20 Now at DESY group FEB, Hamburg, Germany. 21 Also at Institut of Theoretical and Experimental Physics, Moscow, Russia. 22 Also at INP, Cracow, Poland.…”
mentioning
confidence: 99%
“…Calorimeter energy deposits and tracks not previously identified as electron, photon or muon candidates are used to form combined cluster-track objects, from which the hadronic final state is reconstructed [34,38]. Jets are reconstructed from these combined cluster-track objects using an inclusive k T algorithm [39,40] with a minimum transverse momentum of 4 GeV. The missing transverse momentum P miss T in the event is derived from all detected particles and energy deposits in the event.…”
Section: Particle Identification and Event Reconstructionmentioning
confidence: 99%
“…The k T -cluster algorithm known as the Durham jet algorithm [11,12], as implemented in the FastJet package [13], was used for jet reconstruction. It was run in exclusive mode i.e.…”
Section: Jet Selectionmentioning
confidence: 99%